You said what?! : the biggest communication mistakes professionals make - Zoller, Kim; Preston, Kerry (Confident Communicator's Guide., 2015)
Communication is a measure of how we are heard. It's not about us; it is about how the other person perceives our message. If you are not where you should be in your career, the problem may very well be how you communicate. This book gives you solid techniques that can be used right away to achieve effective results, including: quick tips and strategies on communication skills; real-life stories of how business communication can impact your career; tools that help you be understood and heard; strengthening your message by planning and sharpening your communication skills. This edition will help enhance your skills as a facilitator; create supportive and effective learning environments for face-to-face and online learners; ensure learning is transferred to the job. --